(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The National Highways or Toll roads play an important role in connecting different cities. They not only reduce traffic problems but also help to save fuel and precious time of the travellers . These National Highways are maintained and managed by National Highways Authority of India (NHAI) . The NHAI has set up toll plazas which collect the toll taxes from the vehicle drivers who use the National High ways. Besides this, NHAI has kept SOS (save our soul) service boxes along the National Highways to help the toll road Users in case of Emergency. Keeping these in mind , the authors in this article have made an attempt to study the Behaviour of the toll road users in Gudiyattam town. The study has been conducted among 100 respondents who use the toll roads. The authors have adopted convenience sampling method to collect the primary data.